1985
DOI: 10.1029/jc090ic06p11689
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐induced change in a coupled ocean‐atmosphere model and its paleoclimatic implications

Abstract: The climatic effects of very large changes of CO 2 concentration in the atmosphere are explored using a general circulation model of the coupled ocean-atmosphere system. As a simplification the model has an annual mean insolation and a highly idealized geography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
154
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(171 citation statements)
references
References 35 publications
(24 reference statements)
15
154
2
Order By: Relevance
“…Although the precise latitudinal registry may have varied in the geologic past because of different continental distributions, the overall latitudinal width of the equatorial humid belt may be a stable feature of global climate. This is suggested by climate model calculations showing relatively similar latitudinal patterns of P-E for pCO 2 values ranging up to 10 times the preindustrial level (59) and is supported by the paleolatitudinal distribution over geologic time of evaporites, which is approximately the same as occurs today (60). We use a zonally averaged P-E latitudinal profile calculated for 8 ϫ pCO 2 with an idealized geography (59) for the approximate position of the equatorial humid belt in the early Cenozoic (Fig.…”
Section: Weathering Of Deccan Traps In Equatorial Humid Beltmentioning
confidence: 82%
“…Although the precise latitudinal registry may have varied in the geologic past because of different continental distributions, the overall latitudinal width of the equatorial humid belt may be a stable feature of global climate. This is suggested by climate model calculations showing relatively similar latitudinal patterns of P-E for pCO 2 values ranging up to 10 times the preindustrial level (59) and is supported by the paleolatitudinal distribution over geologic time of evaporites, which is approximately the same as occurs today (60). We use a zonally averaged P-E latitudinal profile calculated for 8 ϫ pCO 2 with an idealized geography (59) for the approximate position of the equatorial humid belt in the early Cenozoic (Fig.…”
Section: Weathering Of Deccan Traps In Equatorial Humid Beltmentioning
confidence: 82%
“…12). First, the warming could have accelerated the hydrologic cycle and thus increased rates of chemical weathering (Manabe and Bryan, 1985;Berner, 1994;White and Blum, 1995;Sloan, Bluth, and Filippelli, 1997). This would increase the flux of nutrients (particularly phosphorus) to the oceans and thus help stimulate biological productivity (Pedersen and Calvert, 1990).…”
mentioning
confidence: 99%
“…Another possible dynamical mechanism that might contribute to the resolution of the paradox is the change in advection of heat due to the non-linear equation of state for seawater (Pond and Pickard, 1983) as shown in Manabe and Bryan (1985) and Gough and Lin (1992). In these studies a more vigorous thermohaline circulation was found, under certain conditions, when the temperature gradient weakened.…”
Section: Introductionmentioning
confidence: 74%
“…Manabe and Bryan (1985) found that, in their ocean circulation simulations, the meridional density gradient increased while the temperature gradient decreased. This arises from the non-linearity of the coefficient of thermal expansion for sea water (Pond and Pickard, 1983).…”
Section: Introductionmentioning
confidence: 99%